Climate Change, the Indoor Environment, and Health - Institute of Medicine (The National Academies Press, 2011)
The indoor environment affects occupants' health and comfort. Poor environmental conditions and indoor contaminants are estimated to cost the U.S. economy tens of billions of dollars a year in exacerbation of illnesses like asthma, allergic symptoms, and subsequent lost productivity. Climate change has the potential to affect the indoor environment because conditions inside buildings are influenced by conditions outside them. Climate Change, the Indoor Environment, and Health addresses the impacts that climate change may have on the indoor environment and the resulting health effects. It finds that steps taken to mitigate climate change may cause or exacerbate harmful indoor environmental conditions. The book discusses the role the Environmental Protection Agency (EPA) should take in informing the public, health professionals, and those in the building industry about potential risks and what can be done to address them. The study also recommends that building codes account for climate change projections; that federal agencies join to develop or refine protocols and testing standards for evaluating emissions from materials, furnishings, and appliances used in buildings; and that building weatherization efforts include consideration of health effects. Climate Change, the Indoor Environment, and Health is written primarily for the EPA and other federal agencies, organizations, and researchers with interests in public health; the environment; building design, construction, and operation; and climate issues.

Communicating Science Effectively: A Research Agenda - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Science and technology are embedded in virtually every aspect of modern life. As a result, people face an increasing need to integrate information from science with their personal values and other considerations as they make important life decisions about medical care, the safety of foods, what to do about climate change, and many other issues. Communicating science effectively, however, is a complex task and an acquired skill. Moreover, the approaches to communicating science that will be most effective for specific audiences and circumstances are not obvious. Fortunately, there is an expanding science base from diverse disciplines that can support science communicators in making these determinations. Communicating Science Effectively offers a research agenda for science communicators and researchers seeking to apply this research and fill gaps in knowledge about how to communicate effectively about science, focusing in particular on issues that are contentious in the public sphere. To inform this research agenda, this publication identifies important influences 2013 psychological, economic, political, social, cultural, and media-related 2013 on how science related to such issues is understood, perceived, and used.

Informing an Effective Response to Climate Change - National Research Council (The National Academies Press, 2010)
Global climate change is one of America's most significant long-term policy challenges. Human activity2014especially the use of fossil fuels, industrial processes, livestock production, waste disposal, and land use change2014is affecting global average temperatures, snow and ice cover, sea-level, ocean acidity, growing seasons and precipitation patterns, ecosystems, and human health. Climate-related decisions are being carried out by almost every agency of the federal government, as well as many state and local government leaders and agencies, businesses and individual citizens. Decision makers must contend with the availability and quality of information, the efficacy of proposed solutions, the unanticipated consequences resulting from decisions, the challenge of implementing chosen actions, and must consider how to sustain the action over time and respond to new information. Informing an Effective Response to Climate Change, a volume in the America's Climate Choices series, describes and assesses different activities, products, strategies, and tools for informing decision makers about climate change and helping them plan and execute effective, integrated responses. It discusses who is making decisions (on the local, state, and national levels), who should be providing information to make decisions, and how that information should be provided. It covers all levels of decision making, including international, state, and individual decision making. While most existing research has focused on the physical aspect of climate change, Informing an Effective Response to Climate Change employs theory and case study to describe the efforts undertaken so far, and to guide the development of future decision-making resources. Informing an Effective Response to Climate Change offers much-needed guidance to those creating public policy and assists in implementing that policy. The information presented in this book will be invaluable to the research community, especially social scientists studying climate change; practitioners of decision-making assistance, including advocacy organizations, non-profits, and government agencies; and college-level teachers and students.

Protecting the Health and Well-Being of Communities in a Changing Climate: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
On March 13, 2017, the Roundtable on Environmental Health Sciences, Research, and Medicine and the Roundtable on Population Health Improvement jointly convened a 1-day public workshop in Washington, DC, to explore potential strategies for public health, environmental health, health care, and related stakeholders to help communities and regions to address and mitigate the health effects of climate change. Participants discussed the perspectives of civic, government, business, and health-sector leaders, and existing research, best practices, and examples that inform stakeholders and practitioners on approaches to support mitigation of and adaptation to climate change and its effects on population health. This publication summarizes the presentations and discussions from the workshop.

Science Literacy: Concepts, Contexts, and Consequences - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Science is a way of knowing about the world. At once a process, a product, and an institution, science enables people to both engage in the construction of new knowledge as well as use information to achieve desired ends. Access to science2014whether using knowledge or creating it2014necessitates some level of familiarity with the enterprise and practice of science: we refer to this as science literacy. Science literacy is desirable not only for individuals, but also for the health and well- being of communities and society. More than just basic knowledge of science facts, contemporary definitions of science literacy have expanded to include understandings of scientific processes and practices, familiarity with how science and scientists work, a capacity to weigh and evaluate the products of science, and an ability to engage in civic decisions about the value of science. Although science literacy has traditionally been seen as the responsibility of individuals, individuals are nested within communities that are nested within societies2014and, as a result, individual science literacy is limited or enhanced by the circumstances of that nesting. Science Literacy studies the role of science literacy in public support of science. This report synthesizes the available research literature on science literacy, makes recommendations on the need to improve the understanding of science and scientific research in the United States, and considers the relationship between scientific literacy and support for and use of science and research.

Wildland Fires: Toward Improved Understanding and Forecasting of Air Quality Impacts: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Wildland fires pose a growing threat to air quality and human health. Fire is a natural part of many landscapes, but the extent of area burned and the severity of fires have been increasing, concurrent with human movement into previously uninhabited fire-prone areas and forest management practices that have increased fuel loads. These changes heighten the risk of exposure to fire itself and emissions (smoke), which can travel thousands of miles and affect millions of people, creating local, regional, and national air quality and health concerns. To address this growing threat, the National Academies brought together atmospheric chemistry and health research communities, natural resource managers, and decision makers to discuss current knowledge and needs surrounding how wildland fire emissions affect air quality and human health. Participants also explored opportunities to better bridge these communities to advance science and improve the production and exchange of information. This publication summarizes the workshop discussions and themes that emerged throughout the meeting.

Facilitating Climate Change Responses: A Report of Two Workshops on Knowledge from the Social and Behavioral Sciences - National Research Council (The National Academies Press, 2010)
The William and Flora Hewlett Foundation, understanding the need for policy makers at the national level to entrain the behavioral and social sciences in addressing the challenges of global climate change, called on the National Research Council to organize two workshops to showcase some of the decision-relevant contributions that these sciences have already made and can advance with future efforts. The workshops focused on two broad areas: (1) mitigation (behavioral elements of a strategy to reduce the net future human influence on climate) and (2) adaptation (behavioral and social determinants of societal capacity to minimize the damage from climate changes that are not avoided). Facilitating Climate Change Responses documents the information presented in the workshop presentations and discussions. This material illustrates some of the ways the behavioral and social sciences can contribute to the new era of climate research.

Advancing the Framework for Assessing Causality of Health and Welfare Effects to Inform National Ambient Air Quality Standard Reviews - National Academies of Sciences, Engineering,; Medicine
As part of its responsibilities under the Clean Air Act, the U.S. Environmental Protection Agency sets National Ambient Air Quality Standards (NAAQS) for the air pollutants carbon monoxide, lead, oxides of nitrogen, particulate matter, ozone, and sulfur dioxide. EPA uses a \

America's Climate Choices - National Research Council
Climate change is occurring. It is very likely caused by the emission of greenhouse gases from human activities, and poses significant risks for a range of human and natural systems. And these emissions continue to increase, which will result in further change and greater risks. America's Climate Choices makes the case that the environmental, economic, and humanitarian risks posed by climate change indicate a pressing need for substantial action now to limit the magnitude of climate change and to prepare for adapting to its impacts. Although there is some uncertainty about future risk, acting now will reduce the risks posed by climate change and the pressure to make larger, more rapid, and potentially more expensive reductions later. Most actions taken to reduce vulnerability to climate change impacts are common sense investments that will offer protection against natural climate variations and extreme events. In addition, crucial investment decisions made now about equipment and infrastructure can \

A Framework for Assessing Effects of the Food System - Institute of Medicine; National Research Council (The National Academies Press, 2015)
How we produce and consume food has a bigger impact on Americans' well-being than any other human activity. The food industry is the largest sector of our economy; food touches everything from our health to the environment, climate change, economic inequality, and the federal budget. From the earliest developments of agriculture, a major goal has been to attain sufficient foods that provide the energy and the nutrients needed for a healthy, active life. Over time, food production, processing, marketing, and consumption have evolved and become highly complex. The challenges of improving the food system in the 21st century will require systemic approaches that take full account of social, economic, ecological, and evolutionary factors. Policy or business interventions involving a segment of the food system often have consequences beyond the original issue the intervention was meant to address. A Framework for Assessing Effects of the Food System develops an analytical framework for assessing effects associated with the ways in which food is grown, processed, distributed, marketed, retailed, and consumed in the United States. The framework will allow users to recognize effects across the full food system, consider all domains and dimensions of effects, account for systems dynamics and complexities, and choose appropriate methods for analysis. This report provides example applications of the framework based on complex questions that are currently under debate: consumption of a healthy and safe diet, food security, animal welfare, and preserving the environment and its resources. A Framework for Assessing Effects of the Food System describes the U.S. food system and provides a brief history of its evolution into the current system. This report identifies some of the real and potential implications of the current system in terms of its health, environmental, and socioeconomic effects along with a sense for the complexities of the system, potential metrics, and some of the data needs that are required to assess the effects. The overview of the food system and the framework described in this report will be an essential resource for decision makers, researchers, and others to examine the possible impacts of alternative policies or agricultural or food processing practices.

Commercial Aircraft Propulsion and Energy Systems Research: Reducing Global Carbon Emissions - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The primary human activities that release carbon dioxide (CO2) into the atmosphere are the combustion of fossil fuels (coal, natural gas, and oil) to generate electricity, the provision of energy for transportation, and as a consequence of some industrial processes. Although aviation CO2 emissions only make up approximately 2.0 to 2.5 percent of total global annual CO2 emissions, research to reduce CO2 emissions is urgent because (1) such reductions may be legislated even as commercial air travel grows, (2) because it takes new technology a long time to propagate into and through the aviation fleet, and (3) because of the ongoing impact of global CO2 emissions. Commercial Aircraft Propulsion and Energy Systems Research develops a national research agenda for reducing CO2 emissions from commercial aviation. This report focuses on propulsion and energy technologies for reducing carbon emissions from large, commercial aircraft2014 single-aisle and twin-aisle aircraft that carry 100 or more passengers2014because such aircraft account for more than 90 percent of global emissions from commercial aircraft. Moreover, while smaller aircraft also emit CO2, they make only a minor contribution to global emissions, and many technologies that reduce CO2 emissions for large aircraft also apply to smaller aircraft. As commercial aviation continues to grow in terms of revenue-passenger miles and cargo ton miles, CO2 emissions are expected to increase. To reduce the contribution of aviation to climate change, it is essential to improve the effectiveness of ongoing efforts to reduce emissions and initiate research into new approaches.

Forest Health and Biotechnology: Possibilities and Considerations - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The American chestnut, whitebark pine, and several species of ash in the eastern United States are just a few of the North American tree species that have been functionally lost or are in jeopardy of being lost due to outbreaks of pathogens and insect pests. New pressures in this century are putting even more trees at risk. Expanded human mobility and global trade are providing pathways for the introduction of nonnative pests for which native tree species may lack resistance. At the same time, climate change is extending the geographic range of both native and nonnative pest species. Biotechnology has the potential to help mitigate threats to North American forests from insects and pathogens through the introduction of pest-resistant traits to forest trees. However, challenges remain: the genetic mechanisms that underlie trees' resistance to pests are poorly understood; the complexity of tree genomes makes incorporating genetic changes a slow and difficult task; and there is a lack of information on the effects of releasing new genotypes into the environment. Forest Health and Biotechnology examines the potential use of biotechnology for mitigating threats to forest tree health and identifies the ecological, economic, and social implications of deploying biotechnology in forests. This report also develops a research agenda to address knowledge gaps about the application of the technology.

Healthy, Resilient, and Sustainable Communities After Disasters: Strategies, Opportunities, and Planning for Recovery - Institute of Medicine
In the devastation that follows a major disaster, there is a need for multiple sectors to unite and devote new resources to support the rebuilding of infrastructure, the provision of health and social services, the restoration of care delivery systems, and other critical recovery needs. In some cases, billions of dollars from public, private and charitable sources are invested to help communities recover. National rhetoric often characterizes these efforts as a \

Limiting the Magnitude of Future Climate Change - National Research Council
Climate change, driven by the increasing concentration of greenhouse gases in the atmosphere, poses serious, wide-ranging threats to human societies and natural ecosystems around the world. The largest overall source of greenhouse gas emissions is the burning of fossil fuels. The global atmospheric concentration of carbon dioxide, the dominant greenhouse gas of concern, is increasing by roughly two parts per million per year, and the United States is currently the second-largest contributor to global emissions behind China. Limiting the Magnitude of Future Climate Change, part of the congressionally requested America's Climate Choices suite of studies, focuses on the role of the United States in the global effort to reduce greenhouse gas emissions. The book concludes that in order to ensure that all levels of government, the private sector, and millions of households and individuals are contributing to shared national goals, the United States should establish a \

Reckoning with the U.S. Role in Global Ocean Plastic Waste - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
An estimated 8 million metric tons (MMT) of plastic waste enters the world's ocean each year - the equivalent of dumping a garbage truck of plastic waste into the ocean every minute. Plastic waste is now found in almost every marine habitat, from the ocean surface to deep sea sediments to the ocean's vast mid-water region, as well as the Great Lakes. This report responds to a request in the bipartisan Save Our Seas 2.0 Act for a scientific synthesis of the role of the United States both in contributing to and responding to global ocean plastic waste. The United States is a major producer of plastics and in 2016, generated more plastic waste by weight and per capita than any other nation. Although the U.S. solid waste management system is advanced, it is not sufficient to deter leakage into the environment. Reckoning with the U.S. Role in Global Ocean Plastic Waste calls for a national strategy by the end of 2022 to reduce the nation's contribution to global ocean plastic waste at every step - from production to its entry into the environment - including by substantially reducing U.S. solid waste generation. This report also recommends a nationally-coordinated and expanded monitoring system to track plastic pollution in order to understand the scales and sources of U.S. plastic waste, set reduction and management priorities, and measure progress.

Behavioral Economics: Policy Impact and Future Directions - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Behavioral economics - a field based in collaborations among economists and psychologists - focuses on integrating a nuanced understanding of behavior into models of decision-making. Since the mid-20th century, this growing field has produced research in numerous domains and has influenced policymaking, research, and marketing. However, little has been done to assess these contributions and review evidence of their use in the policy arena. Behavioral Economics: Policy Impact and Future Directions examines the evidence for behavioral economics and its application in six public policy domains: health, retirement benefits, climate change, social safety net benefits, climate change, education, and criminal justice. The report concludes that the principles of behavioral economics are indispensable for the design of policy and recommends integrating behavioral specialists into policy development within government units. In addition, the report calls for strengthening research methodology and identifies research priorities for building on the accomplishments of the field to date.

Carbon Dioxide Utilization Markets and Infrastructure: Status and Opportunities: A First Report - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Carbon materials pervade many aspects of modern life, from fuels and building materials to consumer goods and commodity chemicals. Reaching net-zero emissions will require replacing existing fossil-carbon-based systems with circular-carbon economies that transform wastes like CO2 into useful materials. This report evaluates market opportunities and infrastructure needs to help decision makers better understand how carbon dioxide utilization can contribute to a net-zero emissions future.

Advancing Health and Resilience in the Gulf of Mexico Region: A Roadmap for Progress - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Consequences of natural disasters and the COVID-19 pandemic have taken a cumulative toll on the health and well-being of people in the Gulf of Mexico region. Long-standing societal challenges related to racism, poverty, education, housing, and underemployment are compounding the trauma, leading to chronic stress for many Gulf residents. The Committee on Progress Toward Human Health and Community Resilience in the Gulf of Mexico Region new report, Advancing Health and Community Resilience in the Gulf of Mexico Region: A Roadmap for Progress, explores key challenges and priorities in Gulf states, including Alabama, Florida, Louisiana, Mississippi, and Texas and evaluates recent progress. The report also makes recommendations for closing critical gaps and implementing transformative approaches that focus on the diverse needs and experiences of people who live and work in the Gulf region.